Diagnóstico de conformidade do processamento de produtos para saúde: análise de indicadores de qualidade na atenção primária a saúde - Roseira, Camila Eugenia (2013)
Health-associated infections (HAI) in non-hospital care is a subject still little explored in literature. Among measures that assist in the prevention and control of HAI is the quality of medical instruments processing which aims to avoid the risks from their use. In order to enable the assessment of medical instruments processing in Primary Health Care (PHC), were adapted and validated quality indicators to assess the practice of medical instruments processing for PHC. Assuming this, it was aimed to diagnose the completeness of the medical instruments processing in PHC health services and assess the usability of the instrument available. This is a study with two arms: the) non-experimental, correlational descriptive and b) methodological study. The hypothesis of this study is that there is difference in the medical instruments processing between Basic Health Units (BHU) and Family Health Centres (FHC). Data collection occurred in the city of São Carlos, in ten health services, selected by convenience. Seven health indicators were applied to evaluate the structure, process and result of that practice. This project was approved by Ethics and Research Committee of UFSCar n° 112,528. The results showed that this activity is a secondary practice in health units observed, because the professionals responsible for this activity are scaled to perform other activities concurrently. There are no records in any health service about medical instruments processing and testing for attesting the effectiveness of the process is not part of routine work. The cleaning process indicator was that had lower overall compliance index (18.18% for BHU and 20.00% for FHC), which deserves attention, given the importance of this step for the subsequent steps. Another point that deserves attention is that literature does not bring standardized information regarding the disinfection of medical instruments, which prevented this component was observed, and therefore suggests an aspect to be studied, so that it can assist professionals responsible for this to carry out disinfection safely for use of medical instruments. Regarding the usability of the indicators, the structure are the most achievable, being followed by the process and result. It should be noted that indicators that require sample are influenced directly by these in terms of implementation time. It is understood the need for studies about this topic on PHC, so that they are established strategies aimed at improving these factors contributing to occupational safety and patient.